2003
DOI: 10.1152/japplphysiol.00485.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fever induction by localized subcutaneous inflammation in guinea pigs: the role of cytokines and prostaglandins

Abstract: In guinea pigs, dose-dependent febrile responses can be induced by injection of a high (100 micro g/kg) or low (10 micro g/kg) dose of bacterial lipopolysaccharide (LPS) into artificial subcutaneously implanted Teflon chambers. In this fever model, LPS does not enter the systemic circulation from the site of localized tissue inflammation in considerable amounts but causes a local induction of the proinflammatory cytokines tumor necrosis factor (TNF) and interleukin-6 (IL-6), which can be measured in lavage flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…Among the pyrogenic cytokines (TNF, IL-1, or IL-6) that are produced within the site of localized subcutaneous inflammation, IL-6 is the only putative endogenous pyrogen that enters the circulation in significant quantities. It has therefore been proposed that the increase of IL-6 in the bloodstream, albeit moderate, is involved in the manifestation of fever and other brain-controlled signs of illness that occur during localized inflammation (9,34,38).However, the following observations from our previous studies (29,30,34) suggested that, in addition to a humoral signal provided by circulating IL-6, local mechanisms generated directly at the site of subcutaneous inflammation may participate in the transmission of febrile signals to parts of the brain that are involved in fever generation. 1) We tested the effects of two doses of LPS (100 or 10 g/kg) injected into the subcutaneous chamber on body temperature.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Among the pyrogenic cytokines (TNF, IL-1, or IL-6) that are produced within the site of localized subcutaneous inflammation, IL-6 is the only putative endogenous pyrogen that enters the circulation in significant quantities. It has therefore been proposed that the increase of IL-6 in the bloodstream, albeit moderate, is involved in the manifestation of fever and other brain-controlled signs of illness that occur during localized inflammation (9,34,38).However, the following observations from our previous studies (29,30,34) suggested that, in addition to a humoral signal provided by circulating IL-6, local mechanisms generated directly at the site of subcutaneous inflammation may participate in the transmission of febrile signals to parts of the brain that are involved in fever generation. 1) We tested the effects of two doses of LPS (100 or 10 g/kg) injected into the subcutaneous chamber on body temperature.…”
mentioning
confidence: 78%
“…However, the following observations from our previous studies (29,30,34) suggested that, in addition to a humoral signal provided by circulating IL-6, local mechanisms generated directly at the site of subcutaneous inflammation may participate in the transmission of febrile signals to parts of the brain that are involved in fever generation. 1) We tested the effects of two doses of LPS (100 or 10 g/kg) injected into the subcutaneous chamber on body temperature.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…We (6,50) and others (12,44) have suggested that, alternatively, PGE 2 could be that mediator. It is synthesized by all macrophages, including Kc, in response to LPS (46), and its levels in plasma are correlated with the febrile course (35).…”
mentioning
confidence: 84%